Institutional Corruption in Russian Universities - Rumyantseva, Nataliya L.; Denisova-Schmidt, Elena (International Higher Education, 2015)
Corruption as traditionally been a part of Russian higher education reality. This article focuses on the institutional aspects of corruption, arguing that the universities need student numbers, and thus permit a certain amount of corruption to enroll and retain them.